Answer:
(-22/7, -41/7)
Explanation:
Please use ( × ) to indicate multiplication and use ( x ) to denote a variable name.
Write out the second equation here:
5x - 2y = 32
Now, we'll apply the "elimination by addition and subtraction" method.
Multiply all three terms of x + y = -9 by -5, obtaining:
-5x - 5y = 9
and then combine this result with the second equation:
5x - 2y = 32
-5x - 5y = 9
-------------------
-7y = 41
Dividing both sides by -7 yields y = -41/7, which is an improper fraction.
I'd suggest you double check to ensure that y ou have copied down this problem correctly.
If we proceed and try to find the value of x, substitute -41/7 for y in
x + y = -9
obtaining:
x - 41/7 = -9, or
x - 41/7 = -63/7
Combining the constants, we get:
x = -22/7
and so the solution is
(-22/7, -41/7)